Pengaruh Peranan Bimbingan dan Konseling Terhadap Kesiapan Kerja Siswa SMK - Arif, Ahmad; Giatman, M.; Syah, Nurhasan; Wagino, Wagino; Saputra, Hendra Dani; Muslim, Muslim; Setiawan, M. Yasep; Hidayat, Nuzul; Sugiarto, Toto (Universitas Negeri Padang, 2023)
The problem in this study is the low work readiness achieved by students who graduated from SMK. The purpose of this study was to determine the work readiness of students of SMKN 1 Batipuh Tanah Datar Regency in terms of the role of guidance in providing career guidance at school. This type of research with a descriptive correlational approach aims to describe and interpret data about the influence of the role of guidance teachers on students' work readiness in the career guidance process at SMKN 1 Batipuh. The research subjects were class XI students of all fields of expertise registered in semester 1 of the 2022/2023 school year at SMKN 1 Batipuh, totalling 52 students. The data analysis technique used is descriptive statistics with percentage calculations and simple regression. The hypothesis in this study is that there is a positive influence between the role of career guidance teachers on the work readiness of students of SMKN 1 Batipuh. The results shown by the value of rxy = 0.568 compared to the interpretation table r, the level of relationship is moderate. Significance obtained titung = 4.816. The test criteria used are tcount> ttable then Ho is rejected and Ha is accepted based on the t-distribution table for degrees of freedom (dk = n-2) 33, obtained ttable = (α = 0.05) = 1.697. Thus Ho is rejected and Ha is accepted, so the hypothesis states